Implementasi Sistem Perpustakaan Yang Terintegrasi Melalui Layanan OPAC di Universitas Negeri Medan - Rahot Martua Rambe; Hannum Angginami; Zaki Fahri; Yusniah Yusniah (Da'watuna: Journal of Communication and Islamic Broadcasting, 2023)
How to implement an integrated library system through OPAC services at Medan State University. The goal of this study is to figure out an integrated library system through OPAC services at Medan State University. This study employed a qualitative research approach that made use of primary data. The results of this study are the use of OPAC in the Medan State University library significantly improves the performance of librarians, students, and library visitors with OPAC. Save time and very effective. Keywords: Library, Integration Library System, OPAC